Dielectric Properties of Upside-Down SrTiO3/Li2MoO4 Composites Fabricated at Room Temperature - Kuzmić, Nina; Škapin, Srečo Davor; Nelo, Mikko; Jantunen, Heli; Spreitzer, Matjaž (Frontiers in Materials, 2021)
In this paper, ceramic upside-down lithium molybdate-strontium titanate (LMO-ST) composites fabricated at room temperature are described. Room temperature fabrication (RTF) is a promising alternative to the time- and energy-consuming high-temperature sintering of electroceramics, which involves mixing of the initial phases, molding with a steel dye, pressing, and drying, while in the last two phases the action of densification takes place. The LMO-ST composites are based on a high ratio of filler ST, coupled with the corresponding LMO binder. Part of the binder is admixed to the ceramic particles and additional part is added as a saturated aqueous solution, which crystallizes during pressing and drying, leading to its deposition on the surface of the filler particles. As a result, sufficient binding with 76–84% relative density was achieved. The deeper insight into the method was provided by various processing aspects and corresponding microstructural investigations. The particle size distribution, pressure, pressing time, ultrasonic treatment, drying time and processing conditions were optimized to obtain improved functional properties of the LMO-ST composites. The results of this study with relative permittivity in the range of 65–78 and dielectric loss tangent values of 0.002–0.05 can attract considerable attention for the use of LMO-ST composites in the industry of electroceramics.